Optimization of rice husk ash-based geopolymers coating composite for enhancement in flexural properties and microstructure using response surface methodology - Mohd Basri, Mohd Salahuddin; Mustapha, Faizal; Mazlan, Norkhairunnisa; Ishak, Mohamad Ridzwan (MDPI, 2020)
If the coating is sufficiently flexible, no tears, cracks, or debond will occur. Although geopolymers have a great potential as a coating material, research on the flexural properties is very limited. In this study, a three-point bending test and scanning electron microscope were used to investigate the flexural properties and microstructure of the geopolymer composite coating (GCC), respectively. Response Surface Methodology (RSM) consists of a combination of mathematical and statistical techniques, which is useful in modelling, analyzing, and optimizing responses that are influenced by several factors. It was used in determining the relationship between each factor and determining the best composition for the composite coating. Several factors were considered including ratio of activated alkaline (AA) solution (V1), RHA/AA ratio (V2), and curing temperature (V3). Results showed that the RHA/AA ratio mostly influenced the response, followed by curing temperature while the ratio of AA was not significant. Lower V2 and V3 values provided the highest flexural strength and modulus. The optimum composition which provided the best coating of flexural properties were V1 = 3.5, V2 = 0.39, and V3 = 45.7 °C. Microscopic images showed that coating with high flexural properties (ductile coating) exhibited minor and rough cracks as compared to that of coating with low flexural properties (brittle coating) which displayed a crack with a clean linear cut. Brittle coating was highly agglomerated and has a significant negative effect on the flexural properties. By developing the optimum composition, the GCC may potentially be a good alternative as a building construction coating material.